Exploring the Role of Macroalgal Surface Metabolites on the Settlement of the Benthic Dinoflagellate Ostreopsis cf. ovata - Ternon, Eva; Paix, Benoît; Thomas, Olivier P.; Briand, Jean-François; Culioli, Gérald (Frontiers in Marine Science, 2020)
Macroalgae constitute one of the preferred substrates of the benthic dinoflagellate Ostreopsis cf. ovata. Across the Mediterranean Sea, this toxic microalga has been shown to thrive on the surface of various species of macroalgae, including Chlorophyta, Rhodophyta and Phaeophyceae. Interestingly, some Dictyotaceae are characterized by a low abundance of cells of O. cf. ovata on their surface. Based on the antifouling properties of some specialized metabolites produced by seaweeds, macroalgal metabolites have been proposed to contribute to the settlement and development of O. cf. ovata. To address this question, the composition of the surface of four Dictyotaceae, Dictyota dichotoma, Dictyota spiralis, Taonia atomaria and Padina pavonica was investigated through an integrative approach combining the analysis of their eukaryotic diversity (18S rRNA gene metabarcoding), their surface metabolome (untargeted LC-MS-based metabolomics) as well as the bioactivity of their surface extracts on O. cf. ovata. Altogether, the data suggest an influence of the macroalgal surface chemistry on the growth of the dinoflagellate, with D. dichotoma being the most bioactive. Some metabolites are proposed to be involved in the observed bioactivity. Other biotic factors are also likely to be entailed in the control of the O. cf. ovata population and they may even prevail on the influence of the macroalgal surface chemistry.